Comparison of feedlot performance of steer calves produced by Angus x Hereford and Brahman x Hereford cows - J.R. Brethour; D. Patterson; K. Olson; L. Corah (Kansas Agricultural Experiment Station Research Reports, 1988)
Steer calves that were 75 percent Hereford and either 25 percent Angus (BWF) or Brahman (BRX) were compared in a feedlot study that involved either high-concentrate or high-silage finishing rations. The BRX steers gained significantly faster, but there was no concomitant response in feed efficiency. The ration energy utilization by BRX steers appeared to be less than that of BWF steers. Performance of both breeds was poorer on the high-silage ration than on the high-grain ration, and there was no breed by ration interaction. A greater proportion of BWF calves graded USDA choice, but there was little difference between breeds in average cutability grade. Rates of backfat increase were determined with ultrasound scanning and were higher when the high-grain rations were fed. No significant breed effect on fattening rate was detected. Ultrasound was effective in identifying cattle that could be fed for an additional 28 days. During that period, cattle retained for additional feeding gained an equivalent 3.89 pounds per day when gains were adjusted to a constant dressing percentage.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Feedlot; Performance; Steers